A superior coherent perfect absorber and laser constructed from the periodic ring optical waveguide network based on extremum spontaneous PT-symmetric breaking points - Yao Zhang; Xiangbo Yang; Mengli Huang (Scientific Reports)
Abstract In this study, we propose a superior coherent perfect absorber and laser (CPA laser) constructed from the one-dimensional (1D) two-material (TM) parity-time (PT) symmetric periodic ring optical waveguide network (PROWN). A novel method based on seeking the exact extremum spontaneous PT-symmetric breaking points is used for determining the imaginary part of the refractive indices of the materials composed of waveguides. The minimal overall output coefficient $${Θ _{\min }}$$ and maximal transmissivity $${T_{\max }}$$ can reach $$3.1914× {10^{- 16}}$$ and $$1.5667× {10^{15}}$$ , respectively, which are 9 orders of magnitude smaller and larger than the previously reported values, respectively. It is also found that with the increment of unit cells, $${Θ _{\min }}$$ increases monotonically while $${T_{\max }}$$ decreases monotonically. Moreover, $${Θ _{\min }}$$ and $${T_{\max }}$$ are found to be varied with the periodicity of 1.866152 MHz. Our work provides a new method for optimizing CPA lasers.